Pola Komunikasi Orang Tua Dengan Remaja Depresi Di Surabaya - Angelia, Shebrina Fathea (Peneliti.net, 2024)
This study is a qualitative research aimed at analyzing the communication patterns between parents and adolescents experiencing depression using the theory proposed by Diana Baumrind. The data collection technique employed in this research involved in-depth interviews with 6 informants (3 family pairs), consisting of 3 parents and 3 adolescents. The study revealed that the authoritarian communication pattern applied by parents can exert pressure on adolescents, causing them to feel unsafe in expressing their feelings. As a result, adolescents choose to internalize their emotions, and over time, this emotional burden can accumulate, triggering or exacerbating the depressive condition in adolescents. It is crucial for parents to adopt effective communication patterns with their adolescents, allowing them to open up and minimizing the occurrence of depression in teenagers.